Homes as "cages of violence" during the COVID-19 pandemic: A pastoral care approach to the case of Botswana - Madigele, Tshenolo J. (HTS teologiese studies, 2022)
Violence has become a common phenomenon that affects women and children, particularly during the coronavirus disease 2019 (COVID-19) pandemic. While the lockdown regulations were meant to save lives by preventing further spread of the virus, another virus called ‘violence against women’ encroached the space which is supposed to be the safest for women and children. For women, homes have now been turned into cages of violence and slaughterhouses. Toxic masculinity is seen at play as all dominant and power ideologies are employed against women. This article deals with these challenges of violence against women in Botswana from a pastoral care point of view. Firstly, it provides an overview of the current gender-based violence (GBV) situation in Botswana through empirical data from other social scientists. It then highlights some forms and the causes linked to the problem of GBV in Botswana. Secondly, it brings in pastoral care work, particularly mutual care, as a relevant tool for the church in addressing GBV. Lastly, it suggests ways in which the church could contribute in pursuit of gender justice and building a violence-free society.Contribution: While the article grapples with the challenges of GBV and persistent toxic masculinities from a theological point of view, the implications of the outcome are multidisciplinary. They aim to respond and raise awareness about the need to build a violence-free society, and to deal with the challenges of oppression, toxic masculinity and manhood ideologies which result in the domination and killing of women.